Exploring the Experiences of Individuals Who are Blind or Low-Vision Using Object-Recognition Technologies in India - Morrison, Cecily (CHI 2025, 2025)
Assistive technologies, such as smartphone-based object-recognition (OR) apps, provide visual assistance to people who are blind or low vision to enable increased independent participation in society. While previous research has explored the functional accessibility of object-recognition technologies, little attention has been given to their social accessibility, particularly in interdependent sociocultural contexts of the Global South. Through a mixed-methods approach, employing a seven-day diary study followed by one-on one interviews with seven OR app users in India, we explore their experiences in depth. Our findings highlight the nuances of what interdependence looks like in a multicultural, Indian society, as people navigate public and private spheres with a camera-based assistive technology designed for independent, western contexts. We argue for the necessity to design assistive technologies following the interdependence framework that accommodates the social and cultural context of the Global South. Additionally, we propose design guidelines for assistive technologies in community-oriented societies, emphasizing community-centered approaches, cultural alignment, and locally adaptable designs.